2016
DOI: 10.3390/su8090854
|View full text |Cite
|
Sign up to set email alerts
|

Synergy and Transition of Recovery Efficiency of Nitrogen Fertilizer in Various Rice Genotypes under Organic Farming

Abstract: Despite the growing demand for organic products, research on organic farming (OF) such as genotype screening, fertilizer application and nutrition uptake remains limited. This study focused on comparisons of the apparent recovery efficiency of nitrogen fertilizer (REN) in rice grown under OF and conventional farming (CF). Thirty-two representative conventional Japonica rice varieties were field grown under five different treatments: control check (CK); organic farming with low, medium and high levels of organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It has been reported that the Chl and N concentrations determined in the laboratory have high correlations with the SPAD readings for a variety of plant species, including: corn (Hurtado et al, 2010), tomato (Ferreira et al, 2006), cabbage (Westerveld et al, 2003), rice (Huang et al, 2016) and mangrove (Dou et al, 2018). High correlations have also been reported with atLEAF meter in corn, wheat (Zhu et al, 2012) and sage (Dunn et al, 2018a).…”
Section: Design and Statistical Analysismentioning
confidence: 99%
“…It has been reported that the Chl and N concentrations determined in the laboratory have high correlations with the SPAD readings for a variety of plant species, including: corn (Hurtado et al, 2010), tomato (Ferreira et al, 2006), cabbage (Westerveld et al, 2003), rice (Huang et al, 2016) and mangrove (Dou et al, 2018). High correlations have also been reported with atLEAF meter in corn, wheat (Zhu et al, 2012) and sage (Dunn et al, 2018a).…”
Section: Design and Statistical Analysismentioning
confidence: 99%
“…A study suggests that organic farming practice slows the decline in key enzymes of nitrogen metabolism in organic nitrogen-efficient type rice, thus maintaining a relatively high capacity for nitrogen uptake and utilization and increasing yield during the late growth period. Cultivating selected cultivars varieties of rice with the synergistically high efficiency of nitrogenous fertilizer and high grain yield under organic farming is able to increase the efficiency (Huang et al , 2016).…”
Section: Resultsmentioning
confidence: 99%
“…When comparing organic and conventional food, the first thing that it must have been borne in mind the fact that the market for organic food and its production is constantly growing (IFOAM, 2020). Higher demand for organic products, as well as, political support is affecting the growth of the organic food market (Huang et. al., 2016).…”
Section: Introductionmentioning
confidence: 99%